Halal Logo, Beauty Blogger & Halal Marketing Package : Which One is the Most Influencing Factors that Lead into Purchase Decision on Halal Cosmetic - Utami Putri, Telisiah (International Journal of Engineering and Technology, 2018)
Halal cosmetic becomes more popular today, and soon or later shall be perceived as a necessity. Halal products themselves are identical with the presence of halal logo on the product or packaging, however does halal logo enough to stimulate consumer to choose a certain halal cosmetic brand?.Consumer nowadays are exposed with more options of communication from many brands, both digital and non-digital media are presented to today’s consumer, in response to current situation manufacturer has to understand kind of media that might significantly affect their consumer behavior. In digital media the presence of beauty bloggers are started to get consumer’s attention and suddenly become a new reference for seeking information of a new product, however the presence of convential halal marketing package is still undeniable, kind of models with hijab and Islamic message on the communication of is also considered  play significant role in building consumer perceptions.This study aims to find out whether halal logo, beauty blogger or conventional halal marketing package is the most significant factor to create consumer positive perception that will ultimately determine purchase decision to buy halal cosmetic products.The study is conducted in Jakarta and Surabaya via on-line survey through WhatsApp mobile application to those active users of social media ages 20-50 y.o and using mass-market cosmetic. Mobile application  is chosen in order to get spesific target respondents who are members of social media. Using structural questionnaire, up loaded digitally by using Google forms, that been delivered by using smartphone through WhatsApp mobile application within 1 week of field study.Findings reveals if conventional halal marketing package is still more significant to create positive perception, followed with Halal logo and beauty blogger.